RIDHA TERHADAP CITRA TUBUH PADA REMAJA - Kiptiah, Mery Atul (Jurnal Studia Insania, 2018)
The aim of the study is the prove Ridha relationship to body image in students High school. The incompatibility of body conditions with an ideal body image encourages adolescence to change body shape so that confidence increases. This behavior is the implementation of negative body image so that adolescence need to increase self-acceptance or Ridha. Correlational research type with a quantitative approach. The sample population of student class XI and using purposive sampling with a total of 124 samples. Research data collected using the Ridha scale and body image consisting of 26 and 22 valid items with a reliability coefficient of 0,859 and 0,834. The results showed that there is a positive relationship between Ridha with the body image of adolescents which means the higher Ridha then the more positive body image with correlation coefficient rxy=0,324; p=0,000 (p<0,01). R-Square obtained by 0,105 means that being Ridha to contribute effectively is 10,5% to body image.